A Novel Ranking Method for Trapezoidal Fuzzy Soft Sets and Applications in Multicriteria Decision-Making - null P. G. Patil; Vyshakha Elluru; Sunil Jacob John; Baiju T. (Advances in Fuzzy Systems)
Fuzzy set theory is a versatile concept that finds applications in various fields such as mathematics, engineering, control engineering, computer science, and artificial intelligence. When there is uncertainty in the data and/or information available to make a decision, fuzzy numbers play a significant role. They have a major influence on the decision-making process. Hence, the ranking of fuzzy numbers become more significant in solving such problems. As the uncertainty becomes more, the role of fuzzy soft sets plays an important role. There are many ranking techniques for fuzzy numbers but it is necessary to rank the trapezoidal fuzzy soft sets (TrFSSs) to deal with uncertainty. The present paper focuses on introducing a novel ranking method specifically designed for TrFSSs. Furthermore, some examples are presented illustrating the application of this ranking method. Furthermore, the paper explores the use of the proposed ranking method in solving the multicriteria decision-making problems. So far, this is the first ranking method for TrFSSs.